Adenosine Stress Induced Left Bundle Branch Block During Technetium-99m Tetrofosmin Myocardial Perfusion Imaging - Jayanthi, Mohan Roop (World J Nucl Med, 2017)
The occurrence of left bundle branch block (LBBB) in electrocardiogram during exercise testing is a relatively rare finding. The incidence of LBBB during exercise testing ranges from 0.5% to 1.1%. The mechanism of exercise-induced LBBB (EI-LBBB) is poorly understood, but ischemia is a proposed etiology. Stress myocardial perfusion imaging (MPI) can be useful in patients with EI-LBBB to rule out coronary artery disease. Adenosine vasodilator stress is the preferred mode of stress in patients with LBBB for performing stress-MPI. Here we present an interesting case of adenosine-induced LBBB during stress-MPI in a 67-year-old female patient with normal coronary angiography.